Knowledge and Awareness of Basic Life Support among Medical Staffs of Birat Medical College and Teaching Hospital - Arjyal, Batsalya; Rajbanshi, Lalit Kumar; Khanal, Kanak; Bajracharya, Akriti (Birat Journal of Health Sciences, 2019)
Introduction: It is essential that all the medical professionals should have adequate skill for basic life support (BLS) for better outcome of cardiac arrest patients. The objective of the study is to assess the knowledge and awareness of BLS among the medical doctors, nursing staffs and health care paramedics working in Birat Medical College and Teaching Hospital, Biratnagar. Methodology: A three-month duration observational questionnaire-based survey was conducted at Birat Medical College and Teaching Hospital, Biratnagar to assess the knowledge, awareness of basic life support among the medical doctors, nursing staffs and health care paramedics. A total of ten questions were designed to assess the knowledge and awareness regarding BLS skill. Three questions were designed to assess the previous experiences on cardiac arrest situation and BLS training. Similarly, two additional questions were added to assess the self-grading of BLS knowledge which included poor, below average, good and excellent. Result: It was observed that only 14% participants had previous BLS training. Surprisingly, 76% of the participants had encountered cardiac arrest situation in their clinical practice but they were managing those cases with limited knowledge on BLS. The correct answer to the self-structured questionnaire were ticked by less than 50% of participants and majority of the participants came below average on self-grading of the knowledge and awareness suggesting the need of easy accessibility of BLS training centers in the eastern part of Nepal. Conclusion: This study revealed that the knowledge and awareness of basic life support skills among the various staffs was mostly below average to poor. Significant amount of cost effective BLS trainings must be conducted so as to develop competent staffs by various training centers